Concerns and Self-Confidence of Blind Individuals in Karanganyar - Rosyidah, Anifatur; Subagya, Subagya; Supriyadi, Supriyadi (Department of Special Education, 2024)
This study aims to determine the relationship between worry and self-confidence of blind individuals at Yayasan Rumah Hebat Karanganyar. This study is a quantitative correlational study. The subjects of this study were 30 blind individuals who are members of Yayasan Rumah Hebat Fatonah aged 16-42 years. The sampling technique used was non-probability sampling with saturated sampling. The data collection technique in this study used two Likert scale instruments consisting of worry and self-confidence questionnaires. The questionnaire used to measure the level of worry of blind individuals was the Worry Domain Questionnaire (WDQ) formulated by Tallis (1992) with significant validity test results (p p (0.05), then Ho is accepted and Ha is rejected. So that the worry variable with the self-confidence variable has a very low correlation or is not correlated. Based on the results of the analysis test, there is no relationship between worry and self-confidence of blind individuals at the Rumah Hebat Fatonah Karanganyar Foundation.